Commentary on “Targeted release of a bispecific fusion protein SIRPα/Siglec-10 by oncolytic adenovirus reinvigorates tumor-associated macrophages to improve therapeutic outcomes in solid tumors” - Marc Lecoultre; Aya El Helali (Journal for ImmunoTherapy of Cancer)
Tumor-associated macrophages (TAMs), long exploited by cancers to evade immune detection, can now be reprogrammed into potent antitumor effectors through cutting-edge viral engineering. In a landmark study published in the Journal for Immunotherapy of Cancer, Zhang et al introduced an innovative adenovirus, Adv-mSS, that blocks two critical “don’t eat me” signals, CD47 and CD24, used by tumors to paralyze macrophage activity. By converting immunosuppressive TAMs into tumor-engulfing predators and reigniting CD8 T-cell response, Adv-mSS eradicated tumors across multiple preclinical models. This strategy offers a promising avenue for activating both innate and adaptive immunity against cancer and may address key limitations of current immunotherapies.